PAYAKUMBUH CITY TRADITIONAL VIRTUAL MARKET: SUBSYSTEM PERSONAL SHOPPER APPLICATION - KASTOGI, GERRY
The decline in the number of buyers in the traditional market has an impact on the decline the seller's income. This seller's earnings decrease will indirectly affect the Government. The location of a dirty and distant market becomes one of the factors of decreasing the number of buyers. Therefore, the government in Payakumbuh decided to build a traditional virtual market system to solve this problem. This traditional virtual market system will be developed into three subsystems. First, the subsystem used by the buyer. Second, the subsystem used by personal shopper. Third, the subsystem used by the government. Subsystems that focus on this final project is the subsystem that is used by personal shopper. This subsystem is associated with two other subsystems. The functional requirements of this subsystem are the management of shopping carts, the allocation of personal shopper, the change of order status and the calculation of the tariffs charged on each order. Based on the results of analysis that has been done for the management of shopping cart then a shopping cart is managed by a personal shopper. Personal shopper who oversees managing an order or shopping cart is allocated by using several methods. Methods used include allocation based on the number of orders already allocated and allocations based on the distance between buyers. The algorithm used for distance allocation is the K-Means clustering algorithm. After the order is allocated to the personal shopper, the tariff to be paid by the buyer is based on the basic rate and the distance that must be taken by the personal shopper. There are three conclusions that can be drawn from this final project. First, the management of resources is very important in the traditional virtual market system developed, due to the limited number of personal shopper on duty. Second, the time used to run the job scheduler should be adjusted to the state of a region. Third, the ease of customization becomes important so that the system can adapt to the rules that apply in a region.